Dinamika Peran Civil Society dalam Ruang Publik: Studi Wahana Lingkungan Hidup Indonesia (Walhi) Lampung - Heni Nur Efendi; Yulianto Yulianto; Ita Prihantika (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2019)
This study aims to determine and analyze how the role of civil society as a non-State actor and publik sphere in environmental governance in Bandarlampung. This research is motivated by the amount of environmental pollution and the inportance of the role of a civil society. This study focuses on 4 main issues concerning the role of civil society thich are of concern to researchers namely the collection and dissemination of information about the environment, assessment and monitoring of the environment; advocacy for environmental justice and the community has full rights to every public activity. The result of this study are the implementation of the role of civil society going well but there are several indicators that are not optimal in carryng out their role to cooperate with the community in maintaining environmental conditions. The researcher’s suggestion for the role of civil society as a non-State actor and public sphere in environmental governance is that it is often best to conduct socialization and discussion related to environmental issues with the community and increase public access through community empowerment so that the community will be more active and aware of their environmental potential.